Novas espécies de Staurogyne Wall. (Acanthaceae) para o Brasil - Braz, Denise Monte; Monteiro, Reinaldo [UNESP] (FapUNIFESP (SciELO), 2006)
The genus Staurogyne Wall. comprises about 140 tropical species, and in the Neotropics 28 species are recognized, especially found in preserved forested areas. A recent revision of the genus for the Americas revealed four new species in Brazil, which are here described. The new taxa are known from Goiás, Minas Gerais, Espírito Santo, São Paulo, Rio de Janeiro, Paraná and Santa Catarina States, three of them occurring in the Atlantic Rain Forest, and one in the gallery forests of the cerrado domain.
New species of Staurogyne Wall. (Acanthaceae) from Brazil
Keywords: Acanthaceae; Neotropics; Staurogyne; Taxonomy